Photoinduced electron transfer from tris(2,2'-bipyridyl)ruthenium to cytochrome c oxidase. - Nilsson, T (1992)
Flash photolysis has been used to effect electron transfer from tris(2,2'-bipyridyl)ruthenium(II) to cytochrome c oxidase in the presence of a sacrificial electron donor, aniline. The observation that photoreduction occurs only at low ionic strength and high pH indicates that an electrostatic complex between the ruthenium compound and the enzyme is the reactive species. The reaction was followed at 830, 605, and 445 nm. The initial absorbance changes observed suggest that the copper ion CuA is the preferred electron acceptor and that electron transfer from the excited ruthenium complex takes place in less than 1 microsecond. Some rapid cytochrome a reduction is also observed. Absorbance changes after the initial transients suggest that the reduced CuA then equilibrates with cytochrome a with a rate constant of 2 x 10(4) s-1. Comparison of the absorbance changes at 605 and 445 nm and the kinetic difference spectrum in the Soret region indicate that no reduction of cytochrome a3 takes place. With the oxidized enzyme, no further reactions were detected, whereas, in the peroxide and ferryl intermediates, cytochrome a reoxidizes on a millisecond time scale. The reaction appears biphasic in both intermediates, with rate constants in the range 2 x 10(2) to 4 x 10(3) s-1. This is considerably slower than the maximal rates observed for electron transfer between cytochrome a and the bimetallic site found in earlier work and suggests rate limitation by other processes. The rates obtained for the slower phases are close to the rate for catalysis of cytochrome c oxidation.